Fluorescenční korelační spektroskopie - Beranová, Lenka; Humpolíčková, Jana; Hof, Martin (Chemické listy, 2009)
Basic principles of fluorescence correlation spectroscopy (FCS) are explained. The method affords diffusion coefficients and concentrations of fluorescent-labeled species by studying temporary fluctuations of fluorescence signal caused by diffusion through the focal volume of confocal microscope. In dual-color FCS, cross-correlation of two signals from molecules labeled with two spectrally shifted dyes allows to observe interactions between the two molecules. It is also possible to distinguish between the signals of two dyes with different lifetimes. FCS uses pulsed laser excitation.
Keywords: Microscopy, Confocal; mikroskopie elektronová transmisní s filtrací energie; Microscopy, Fluorescence; Microscopy, Energy-Filtering Transmission Electron; konfokální mikroskopie; fluorescenční mikroskopie